Inequality and Growth : A Heterogeneous Approach - Grigoli, Francesco (IMF Working Papers; Working Paper ;, 2016)
The combination of stagnant growth and high levels of income inequality renewed the debate about whether a more even distribution of income can spur economic activity. This paper tests for cross-country convergence in income inequality and estimates its impact on economic growth with a heterogeneous panel structural vector autoregression model, which addresses some empirical challenges plaguing the literature. We find that income inequality is converging across countries, and that its impact on economic growth is heterogeneous. In particular, while the median response of real per capita GDP growth to shocks in income inequality is negative and significant, the dispersion around the estimates is large, with at least one fourth of the countries in the sample presenting a positive effect. The results suggest that the negative effect is mainly driven by the Middle East and Central Asia and the Western Hemisphere across regions, and emerging markets across income levels. Finally, we find evidence that improved institutional frameworks can reduce the negative effect of income inequality on growth.